“Ascribe Power to God, Whose Majesty Is over Israel, and Whose Power Is in the Skies” (Ps 68:35) - Phil J. Botha (Old Testament Essays, 2023)
Psalms 65–68 constitute an editorially arranged and adapted cluster of psalms expressing universal praise and thanksgiving near the end of Book II of the Psalms. The article describes the theological purpose of the four psalms. There is a strong emphasis on God’s presence in the temple in Zion as a source of blessing for his elected people, the cosmos he created and all humanity. Through his magnificent involvement in creation and the history of his people, his fame as creator, righteous judge, and supreme ruler of the world will spread to the ends of the earth. By linking the cluster through keywords with Pss 1–2, the editors demonstrated how God’s benevolent and just involvement with his people would lead to his being universally recognised as the only God.